2012
DOI: 10.1186/1745-9974-8-7
|View full text |Cite
|
Sign up to set email alerts
|

Antitussive effects of the peripherally restricted GABAB receptor agonist lesogaberan in guinea pigs: Comparison to baclofen and other GABAB receptor-selective agonists

Abstract: BackgroundGastroesophageal reflux disease (GERD) is a common cause of chronic cough. Both acid and nonacid reflux is thought to play a role in the initiation of coughing and cough hypersensitivity. The GABAB receptor agonist lesogaberan was developed as a peripherally restricted anti-reflux therapy that reduces the frequency of transient lower esophageal sphincter relaxations (TLESR; the major cause of reflux) in animals and in patients with GERD. GABAB receptor agonists have also been shown to possess antitus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 66 publications
(67 reference statements)
1
15
0
1
Order By: Relevance
“…Baclofen, an agonist at the GABA B receptor, has been shown to inhibit capsaicininduced cough in guinea pigs as well as mechanically stimulated cough in cats in a dose-dependent manner (Bolser et al, 1993). The antitussive effect of baclofen occurs through a central site of action, whereas the GABA B agonists 3-APPi (3-amino-propylphophine) and lesogaberan have been demonstrated to inhibit cough through a peripheral site of action (Bolser et al, 1994;Canning et al, 2012). More recently, microinjections of baclofen into the caudal ventral respiratory group region of pentobarbital-anesthetized, spontaneously breathing rabbits were shown to inhibit mechanically stimulated cough (Mutolo et al, 2010).…”
Section: R Gaba Receptor Agonistsmentioning
confidence: 99%
“…Baclofen, an agonist at the GABA B receptor, has been shown to inhibit capsaicininduced cough in guinea pigs as well as mechanically stimulated cough in cats in a dose-dependent manner (Bolser et al, 1993). The antitussive effect of baclofen occurs through a central site of action, whereas the GABA B agonists 3-APPi (3-amino-propylphophine) and lesogaberan have been demonstrated to inhibit cough through a peripheral site of action (Bolser et al, 1994;Canning et al, 2012). More recently, microinjections of baclofen into the caudal ventral respiratory group region of pentobarbital-anesthetized, spontaneously breathing rabbits were shown to inhibit mechanically stimulated cough (Mutolo et al, 2010).…”
Section: R Gaba Receptor Agonistsmentioning
confidence: 99%
“…Direct inhibitory effects of GABA B receptor agonists on the excitability of vagal afferent nerves in the oesophagus and stomach have been reported [103][104][105]. Interestingly, lesogaberan inhibited inhaled citric acid induced cough in the conscious normal guinea-pig [90], suggesting that this effect may be derived from activation of GABA B receptors perhaps in vagal C-fibres where they have been reported [106,107], and also including effects on vagal afferent nerves in the oesophagus.…”
Section: G-aminobutyric Acid (Gaba) Receptors In Coughmentioning
confidence: 92%
“…A specific receptor antagonist for GABA B receptors, SCH 50911, inhibited the antitussive effects of baclofen in the cat and guinea pig [87]. While this antitussive effect of baclofen is most likely to occur through a central site of action [88,89], other GABA B agonists, 3-APPi (3-amino-propylphophine) and lesogaberan, have been shown to inhibit cough via a peripheral site of action [88,90]. Baclofen when administered not only into the caudal ventral respiratory group but also into caudal aspect of the nucleus tractus solitarius of pentobarbital-anesthetized, spontaneously breathing rabbits inhibited mechanically stimulated cough [91,92], confirming a central mode of action for baclofen.…”
Section: G-aminobutyric Acid (Gaba) Receptors In Coughmentioning
confidence: 99%
“…Canning et al recently evaluated the effect of lesogaberan, a GABA b receptor agonist, in guinea pigs with citric acid induced cough. 22 They reported that both lesogaberan and baclofen reduced coughing in a dose dependant fashion, but lesogaberan did not affect the respiratory rate. In humans, Xu et al recently reported a small case series of 3 patients with chronic cough who responded to baclofen.…”
Section: Other Therapeutic Optionsmentioning
confidence: 98%